2003
DOI: 10.1128/ec.2.1.143-149.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Regulation of Saccharomyces cerevisiae Cell Cycle Genes

Abstract: Nutrient-limited Saccharomyces cerevisiae cells rapidly resume proliferative growth when transferred into glucose medium. This is preceded by a rapid increase in CLN3, BCK2, and CDC28 mRNAs encoding cell cycle regulatory proteins that promote progress through Start. We have tested the ability of mutations in known glucose signaling pathways to block glucose induction of CLN3, BCK2, and CDC28. We find that loss of the Snf3 and Rgt2 glucose sensors does not block glucose induction, nor does deletion of HXK2, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 63 publications
1
55
0
Order By: Relevance
“…Our observations thus far are entirely consistent with previous studies showing that glucose is a potent inducer of CLN3 transcription (22). However, none of the well-known glucose or nutrientsignaling pathways, including cAMP-PKA, TOR, and various glucose transporters, seems to be required for glucose-induced CLN3 transcription (9,22,43). In contrast, the inhibition of glycolysis compromises glucose-induced CLN3 transcription, suggesting a downstream metabolite of glucose could be mediating its effects (9,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations thus far are entirely consistent with previous studies showing that glucose is a potent inducer of CLN3 transcription (22). However, none of the well-known glucose or nutrientsignaling pathways, including cAMP-PKA, TOR, and various glucose transporters, seems to be required for glucose-induced CLN3 transcription (9,22,43). In contrast, the inhibition of glycolysis compromises glucose-induced CLN3 transcription, suggesting a downstream metabolite of glucose could be mediating its effects (9,22).…”
Section: Resultsmentioning
confidence: 99%
“…Cln3p regulates G1 length by coordinating growth and division and may influence cell size when passing Start, the point at which cells commit to division (4)(5)(6)(7). In cln3Δ mutants, cells become larger and stay in the G1 phase longer, resulting in decreased growth and budding rates compared with WT (8,9) (Fig. S1).…”
mentioning
confidence: 99%
“…Because immobilized yeast vigorously ferments glucose during prolonged culture, it has been used for ethanol production, reportedly attaining, relative to planktonic cells, >10-fold increases in volumetric ethanol productivity at high substrate concentrations (65). However, whereas high glycolytic flux typically triggers expression of genes required to pass through G1 (66), immobilized fermentative yeast does not respond to this signal. Indeed, RAS1, which encodes a component of the RAS/cAMP/PKA glucosesignaling pathway, is down-regulated in immobilized relative to planktonic cells, and the gene encoding the transcriptional regulator Rpi1, which acts antagonistically to RAS/cAMP/PKA, is up-regulated (Fig.…”
Section: Two-class Sam Reveals Immobilization-specific Changes In Genmentioning
confidence: 99%
“…Further, it seems that the bottleneck in the upper glycolysis in PGI and PFK results in a smaller flux of carbon downstream, which resembles a deletion of either of the genes PGI1, PFK1, or PFK2 (33, 34). Newcomb et al (35) have studied the relation of flux through glycolysis to the expression of genes encoding for cell cycle regulatory proteins CLN3, BCK2, and CDC28, whose expression causes a passage from phase G 1 (growth 1) into S phase (start). They found that deletion of either gene encoding for PFKe blocks glucose induction of CLN3, BCK2, and CDC28, resulting in a prolonged G 1 and thus slower growth (35).…”
Section: Figmentioning
confidence: 99%
“…Newcomb et al (35) have studied the relation of flux through glycolysis to the expression of genes encoding for cell cycle regulatory proteins CLN3, BCK2, and CDC28, whose expression causes a passage from phase G 1 (growth 1) into S phase (start). They found that deletion of either gene encoding for PFKe blocks glucose induction of CLN3, BCK2, and CDC28, resulting in a prolonged G 1 and thus slower growth (35). In our setup, the expression of cell cycle-related genes CLN3 and CDC28 was also decreased in the lower growth rates in elevated initial mannose concentrations.…”
Section: Figmentioning
confidence: 99%